Combination therapy of rituximab and corticosteroids for patients with refractory chronic immune thrombocytopenic purpura: Report on two cases - Ling, Yun; Qian, Xinyu; Cao, Xiangshan (Contemporary Oncology/Współczesna Onkologia, 2013)
Immune thrombocytopenic purpura (ITP) is an autoimmune disorder, for which rituximab has been proven to be an effective treatment. The response rate was reported to be approximately 60% in refractory ITP patients. However, the response time is slower than expected, and the mechanism of action of rituximab in ITP is still unclear. Thus, sometimes, the use of a combination therapy with rituximab according to different patient conditions is necessary. We report two refractory chronic ITP cases. The two patients were administered a low dose of dexamethasone (10 mg, weekly) combined with rituximab and a smaller dose of prednisone (10 mg, daily) as maintenance therapy. Although their peripheral B cells were almost eliminated, no complete reaction was observed. The maintenance therapy with prednisone was helpful in the prevention of bleeding. The patients’ responses to rituximab treatment suggest that multiple immunological mechanisms are involved in ITP pathogenesis and that the use of a combination therapy with rituximab according to the different patient conditions is necessary.